Impregnation of Norway spruce with low melting-point binary fatty acid as a phase-change material - Grzybek, Jakub; Paschová, Zuzana; Meffert, P.; Petutschnigg, A.; Schnabel, T. (CRC Press/Taylor and Francis Group, 2023)
Norway spruce was impregnated with a eutectic mixture of capric acid and stearic acid. The binary fatty acid was used as a bio-based phase-change material (PCM) for further applications with wood as a latent heat-storage material in building components. For this purpose, different concentrations of impregnation were evaluated. The weight-percentage gain of 124% was the highest for the pure fatty acid mixture, and the PCM-impregnated wood increased density from 470 kg/m3 (untreated wood) to 1045 kg/m3. Compressive strength and hardness were significantly elevated with higher content of fatty acids in the wood. Microscopy analysis confirmed the presence of the PCM within the wood cells. The treated wood also exhibited a larger time delay during heating and cooling due to the temperature shift in the phase transition. Depending on the concentration of the fatty acid in the wood, the latent heat during melting ranged from 50 to 125 J/g in the temperature from about 24oC to 30oC. These results suggest that the use of the capric acid and stearic acid mixture has a great potential to increase the heat-storage capacity of wood and reduce energy consumption for heating and cooling indoor spaces.
Keywords: building components; latentheat-storage; thermal mass; wood impregnation